Guide to restaurants in Manila : friendly dining advice to sink one's teeth into. (Mandaluyong City, Philippines : Encyclea Publication, 2005)
New in this edition is a list of food outlets and caterers, who offer specialties that were tried and tested and heavily recoomende.
Foreword -- Authors and Contributors -- Acknowledgement and Photo Credits -- How to use this Book -- Cuisine -- Maps -- Reviews -- Food Finds.
Keywords: MANILA FOOD GUIDE